Improving graduation rates in drug court: a qualitative study of participants’ lived experiences - Gallagher, John Robert (Criminology & criminal justice, 2017)
For nearly three decades, drug courts have provided a rehabilitative approach within the criminal justice system for individuals who have a substance use disorder. The goal of drug courts is to reduce criminal recidivism, and research has consistently suggested that participants that graduate drug court are less likely to recidivate than those who are terminated from the program. This qualitative study adds to the literature by asking drug court participants (N = 42) their views on the most helpful aspects of the program that support them in graduating and how the program could be more helpful to support them in graduating. Two themes emerged from the data: (1) participants felt that interventions that are common to drug courts, such as drug testing and having frequent contact with the judge, were most helpful in supporting them in graduating the program; (2) participants felt that the agencies that offered treatment for their substance use disorders used punitive tactics and judgmental approaches that compromised the quality of treatment they received, and they felt that this was a barrier to them graduating the program. The findings are discussed in reference to drug court practice.